2007
DOI: 10.1056/nejmoa061235
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Trial of Pulsed Corticosteroid Therapy for Primary Treatment of Kawasaki Disease

Abstract: Our data do not provide support for the addition of a single pulsed dose of intravenous methylprednisolone to conventional intravenous immune globulin therapy for the routine primary treatment of children with Kawasaki disease. (ClinicalTrials.gov number, NCT00132080 [ClinicalTrials.gov].)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
266
1
8

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 394 publications
(285 citation statements)
references
References 28 publications
4
266
1
8
Order By: Relevance
“…2,21 A North American trial assessed the eff ect of addition of a single dose of intravenous methylprednisolone (30 mg per kg) to standard intravenous immunoglobulin and aspirin therapy but, because of the overall low rate of coronary artery abnormalities, was unable to show a signifi cant diff erence in the primary endpoint of the mean Z max score for the right coronary artery and left anterior descending coronary artery combined between groups. 17 In our trial, patients in the infl iximab group had a signifi cantly greater mean reduction from baseline in the Z score of the left anterior descending coronary artery at week 2 compared with the placebo group (SD −0·6 vs −0·3). The small sample size might have precluded detection of other improvements between baseline and subsequent Z scores in the infl iximab group.…”
Section: Albumin (G/l)mentioning
confidence: 59%
See 2 more Smart Citations
“…2,21 A North American trial assessed the eff ect of addition of a single dose of intravenous methylprednisolone (30 mg per kg) to standard intravenous immunoglobulin and aspirin therapy but, because of the overall low rate of coronary artery abnormalities, was unable to show a signifi cant diff erence in the primary endpoint of the mean Z max score for the right coronary artery and left anterior descending coronary artery combined between groups. 17 In our trial, patients in the infl iximab group had a signifi cantly greater mean reduction from baseline in the Z score of the left anterior descending coronary artery at week 2 compared with the placebo group (SD −0·6 vs −0·3). The small sample size might have precluded detection of other improvements between baseline and subsequent Z scores in the infl iximab group.…”
Section: Albumin (G/l)mentioning
confidence: 59%
“…[14][15][16][17][18][19] A meta-analysis of these studies concluded that the addition of corticosteroids to intravenous immunoglobulin resulted in fewer coronary artery abnormalities than with treatment with intravenous immunoglobulin alone (OR 0·3, 95% CI 0·18-0·5). 20 However, heterogeneity in patient selection and treatment protocols severely limits application to our patient population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Авторы считают нецелесообразным добавлять пульс-терапию метилпреднизолоном к стандартной первичной тера-пии ИГВВ [56,57]. В действующем руководстве Аме-ри канской ассоциации сердца рекомендовано огра-ниченно применять глюкокортикоиды только у детей, у которых 2 и более инфузии ИГВВ были неэффективны [15].…”
Section: лечениеunclassified
“…If the body surface area is known, then coronary arteries are normalized to this surface area and expressed as standard deviation units from the mean (Z scores) [44] . Several studies have analyzed CAL using other methods, including the aorta route dimension [12] and transient CAL (although the definition of "transient" varies among studies, from 30 d to 6-8 weeks after disease).…”
Section: Introductionmentioning
confidence: 99%